2015
DOI: 10.1007/s40477-015-0181-2
|View full text |Cite
|
Sign up to set email alerts
|

Inferior vena cava collapsibility loses correlation with internal jugular vein collapsibility during increased thoracic or intra-abdominal pressure

Abstract: IJV and IVC collapsibility correlated during spontaneous breathing but there was no statistically significant correlation during increased thoracic or intra-abdominal pressure. Increased intra-abdominal pressure was associated with a significant smaller maximal IVC diameter and cautions the reliability of IVC diameter in clinical settings that are associated with intra-abdominal hypertension or abdominal compartment syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 20 publications
1
27
1
Order By: Relevance
“…In addition, the reliability of the IVC collapsibility index during increased thoracic or intra-abdominal pressure remains unclear in patients undergoing NIV, as few data are presently available in this setting of patients. 10 Finally, as suggested in our study limitations, we underlined the lacks of hemodynamic data. An assessment by right heart catheterization might have provided more accurate information about RV function and RAP in OSAS.…”
Section: Next According To Task Force Of the American Academy Of Sleepmentioning
confidence: 76%
“…In addition, the reliability of the IVC collapsibility index during increased thoracic or intra-abdominal pressure remains unclear in patients undergoing NIV, as few data are presently available in this setting of patients. 10 Finally, as suggested in our study limitations, we underlined the lacks of hemodynamic data. An assessment by right heart catheterization might have provided more accurate information about RV function and RAP in OSAS.…”
Section: Next According To Task Force Of the American Academy Of Sleepmentioning
confidence: 76%
“…[23] There exists a correlation between the collapsibility of the IVC and the IJV, yet this correlation is heavily dependent on intra-thoracic and intraabdominal pressures at the time of measurement. [24] IJV collapsibility index values over 39% are strongly indicative of volume depletion. A study in 2015 by Bauman et al [24] showed that increased intra-abdominal pressure can cause collapse of the IJV, which could be falsely interpreted as volume depletion.…”
Section: Understanding Measurement Of Ivc (Diameter and Collapsibilitmentioning
confidence: 99%
“…[24] IJV collapsibility index values over 39% are strongly indicative of volume depletion. A study in 2015 by Bauman et al [24] showed that increased intra-abdominal pressure can cause collapse of the IJV, which could be falsely interpreted as volume depletion. Compared to other large veins in the body the IVC still stands as the most evidence-based indicator of volume status.…”
Section: Understanding Measurement Of Ivc (Diameter and Collapsibilitmentioning
confidence: 99%
“…In 2015 [1], the Society of Critical Care Medicine (SCCM) published guidelines for the use of general and cardiac ultrasound [2,3]. roughout the years, most studies have focused on individual organs and systems to evaluate the IVV status, such as examining the right and left heart chambers and contractility [2][3][4], evaluation of the inferior vena cava (IVC) [5][6][7][8][9][10][11] and/or its collapsibility, and the internal jugular vein (IJV) [12][13][14][15] and its respiratory variation, as well as lung water volumes and pulmonary edema [16][17][18][19]. rough literature review, we failed to identify a scoring system or a numerical value to help standardize different exams.…”
Section: Introductionmentioning
confidence: 99%